Pengaruh Stres Kerja Terhadap Kinerja Karyawan Pada Dinas Bina Marga, Cipta Karya dan Tata Ruang Provinsi Sumatera Barat - Anggi Yulianda Sevira; Fisla Wirda; Imelda M. Nur (ABEC Indonesia, 2023)
Efforts to improve employee performance include paying attention to employee job stress levels. This study took the object of research at the Department of Bina Marga, Cipta Karya and Tata Ruang of West Sumatra. The focus of this research is on the field of Bina Marga, which is the field of technical implementation of planning, construction and maintenance of roads and bridges. The purpose of this study was to determine the effect of work stress on employee performance at the Department of Bina Marga, Cipta Karya and Tata Ruang of West Sumatra. This study used a quantitative approach with data collection techniques through questionnaires. Respondents examined in this study totaled 51 respondents who were employees of the Bina Marga sector who were obtained using census techniques. Then an analysis of the data obtained using simple linear regression analysis was carried out. The results of this study indicate that the level of work stress is at 55.5% with a fairly good category and employee performance is at 76.3% with a good category. Based on the results of the analysis, work stress has a negative and significant effect on employee performance. Work stress affects employee performance by 25.4%.   Keywords: Job Stress, Employee Performance